The Role of Dividend Policy in Moderating the Influence of Investment Decisions, Profitability, and Financing Decisions on the Firm Value in the Mining Sector - Owen Noriega Setyo Raharidan; Fitriyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The mining sector has always attracted investors due to its distinct nature compared to other industrial sectors. Stocks in this sector tend to rise along with the demand for mining materials and the decreasing availability of mining resources. Investors are not only interested in stock prices but also in other factors. This research aims to determine the effect of dividend policy in moderating the impact of investment decisions, profitability, and financing decisions on the firm value in the mining sector. This study uses a quantitative approach, with a total population of 62 companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample was selected using the purposive sampling method, resulting in 18 companies that meet the predetermined criteria. The data analysis process involves multiple linear regression using SPSS software. The results show that investment decisions, profitability, and financing decisions influence the firm value of mining companies in Indonesia. However, when dividend policy is used as a moderating variable, investment decisions, profitability, and financing decisions no longer have a significant effect on firm value. This is because the significance values between the independent variables and the dependent variable are better without the moderating variable. Thus, this indicates that the moderating variable is unable to mediate between the independent variables and the dependent variable.